SELF-DETERMINATION AND COLLEGIALITY - BASES OF FORMATION AUTHOR’S SCIENTIFIC SCHOOL - Козлакова, Галина Олексіївна; Саєнко, Тетяна Василівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
Proposed an analytical overview of the stages of formation of the author’s scientific school, selected areas of research, the successful operation of their conditions and the impact on the development of the national higher education system